2016
DOI: 10.1038/srep26765
|View full text |Cite
|
Sign up to set email alerts
|

Pcdh19 Loss-of-Function Increases Neuronal Migration In Vitro but is Dispensable for Brain Development in Mice

Abstract: Protocadherin 19 (Pcdh19) is an X-linked gene belonging to the protocadherin superfamily, whose members are predominantly expressed in the central nervous system and have been implicated in cell-cell adhesion, axon guidance and dendrite self-avoidance. Heterozygous loss-of-function mutations in humans result in the childhood epilepsy disorder PCDH19 Girls Clustering Epilepsy (PCDH19 GCE) indicating that PCDH19 is required for brain development. However, understanding PCDH19 function in vivo has proven challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
108
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(131 citation statements)
references
References 28 publications
20
108
3
Order By: Relevance
“…We also examined localization of exogenously expressed Pcdh19 in hippocampal neurons and found that, unlike the endogenous protein, most of the exogenously expressed Pcdh19 colocalized with Homer-1 at spine-like processes (Fig. 3f, arrows), as reported previously 19 . These results suggest that, although Pcdh19 is capable of localizing to spines or synapses in certain physiological or artificial conditions such as overexpression, this protein is not a constitutive component of synapses.
Figure 3Distribution of Pcdh19 along dendrites of hippocampal neurons.
…”
Section: Resultssupporting
confidence: 78%
“…We also examined localization of exogenously expressed Pcdh19 in hippocampal neurons and found that, unlike the endogenous protein, most of the exogenously expressed Pcdh19 colocalized with Homer-1 at spine-like processes (Fig. 3f, arrows), as reported previously 19 . These results suggest that, although Pcdh19 is capable of localizing to spines or synapses in certain physiological or artificial conditions such as overexpression, this protein is not a constitutive component of synapses.
Figure 3Distribution of Pcdh19 along dendrites of hippocampal neurons.
…”
Section: Resultssupporting
confidence: 78%
“…Such a mechanism could apply to the superior colliculus, which also has a columnar functional organization. Additionally, a similar radial organization has recently been shown in the developing mouse cortex, in which a LacZ knockin to the PCDH19 locus reveals radial stripes (Pederick et al 2016). This mechanism does not appear to be limited to δ-pcdhs, as retinal progenitor cells that express Cdh6 have been shown to generate cdh6- positive clones that include retinal ganglion cells, amacrine cells, bipolar cells, horizontal cells and photoreceptors (De la Huerta et al 2012).…”
Section: Neurogenesis and Neuronal Migrationsupporting
confidence: 67%
“…134,135 FOXG1 mutations share some overlapping features with MECP2-related disease. 18,137 PCDH19 mutations, which encodes a protein highly expressed in the brain, important for cell-cell adhesion, axon guidance, and dendrite self-avoidance, 138 are well known to lead to DEE and later-onset epilepsy in females, characterized by focal and/or generalized seizures that typically occur in clusters. 135 Unlike the MECP2 X-linked inheritance pattern (and consequential female predominance) both sexes are relatively equally affected.…”
Section: Epilepsy Syndromes Associated With Prominent Stereotypiesmentioning
confidence: 99%